Investigation of the deamidation reaction in the enzyme triosephosphate isomerase by means of computational chemistry tools - Uğur, İlke. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2014., 2014)
Deamidation is the posttranslational modi cation of asparagine (Asn) and glutamine (Gln) residues, which is observed in several proteins and peptides. It has been shown that deamidation limits the lifetime of these macromolecules. In this work, deamidation of asparagine in small peptides and in the enzyme triosephosphate isomerase has been modeled. Deamidation in mammalian triosephosphate isomerase has been observed at two distinct deamidation sites: Asn15 and Asn71. Asn71 deamidates faster than Asn15 and slower than a small peptide. Deamidation at Asn15 is supposed to occur with the in uence of deamidated Asn71. In order to explain these experimental ndings, microsecond long classical molecular dynamics simulations and free energy calculations using quantum mechanics/molecular mechanics tools combined with umbrella sampling technique have been performed. The sequential deamidation in triosephosphate isomerase has been shown to be related with both global and local e ects. These results bring a new perspective to the impact of the high-order structure on deamidation rate. The most plausible route of this reaction was also determined. The pKa shift of backbone amide of the residue adjacent to asparagine has been found to be one of the most crucial factor determining the rate of deamidation. Considering the importance of pKa shifts in protein environment, a computational protocol was suggested in order to obtain accurate and fast pKa predictions. This protocol was applied to small organic molecules, and it has been shown to be applicable to studies concerning aminoacid pKa predictions.
Keywords: Deamination.; Proteins -- Deamination.